1987
DOI: 10.1248/cpb.35.1138
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Tumor Cell Cytotoxicity and Serine Protease Activity of Peritoneal Macrophages from Mice Treated with Bakers' Yeast Mannans

Abstract: Peritoneal exudate cells (PEC) from C3H/He mice given bakers' yeast mannans, WNM and WAM025, showed marked cytolytic activity against MM46 tumor cells in vitro. Because the cytotoxicity of the PEC was strongly inhibited by actinomycin D, it was assumed that the cytolytic factor was a proteinous material(s). Of the macrophages and polymorphonuclear leucocytes (PMN ) separated from the PEC, only the former cells were found to display cytolytic activity. Quinacrine, a phospholipase A2, inhibitor, and sodium azide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…It is possible that the protective effect of WAM025 depends on the production of IL-1 (Tables 1, 2) by the activated KC, in addtition to the other previously reported factors. [13][14][15]19) The results in Table 2 show that WAM025 could directly activate the production of IL-1 by KC obtained from a normal mouse.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is possible that the protective effect of WAM025 depends on the production of IL-1 (Tables 1, 2) by the activated KC, in addtition to the other previously reported factors. [13][14][15]19) The results in Table 2 show that WAM025 could directly activate the production of IL-1 by KC obtained from a normal mouse.…”
Section: Discussionmentioning
confidence: 98%
“…Our data confirm the importance of serine proteases as a host-immune protective mechanism. 19,23) It is also suggested that the adjuvant effects of WAM025 [13][14][15]19) may in part be mediated via its ability to augment the number of and the IL-1 production by KC. Of the yeast polysaccharides, WAM025 should be a useful biological response modifier in the defense system of tumor-and infectious disease-bearing hosts.…”
Section: Discussionmentioning
confidence: 99%